Underwriting Technology Trends: A Systematic Literature Review - Budy Santoso, Cahyono; Ghaniy, Rajib (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2024)
This study systematically reviews trends in underwriting technology to enhance the precision and personalization of insurance companies' risk assessment and decision-making processes. Using the Kitchenham method, we conducted a systematic review of scientific publications indexed by Scopus from 2011 to 2021. Our findings reveal the extent of research activity in this field, the leading contributing countries, the methodologies employed, the technologies utilized, and the specific areas investigated. The results indicate significant advancements in the application of machine learning, blockchain, and other technologies in underwriting, providing a comprehensive overview of current trends and future directions. This study offers valuable insights for researchers and practitioners aiming to improve underwriting technology, highlighting potential areas for further research and development. These insights are crucial for advancing the field and enhancing the efficiency and effectiveness of underwriting practices.